2019
DOI: 10.1002/jms.4438
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the ligstroside aglycone isoforms in virgin olive oils by liquid chromatography–high‐resolution Fourier‐transform mass spectrometry and H/Dexchange

Abstract: A systematic structural characterization of the isomeric forms related to ligstroside aglycone (LA), one of the most relevant secoiridoids contained in virgin olive oils, was performed using reverse phase liquid chromatography with electrospray ionization Fourier‐transform single and tandem mass spectrometry, operated in negative ion mode (RPLC‐ESI(−)‐FTMS and FTMS/MS). The high mass resolution and accuracy provided by the adopted orbital trap mass analyzer enabled the recognition of more than 10 different iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 33 publications
8
37
0
Order By: Relevance
“…The latter were able to explain the generation of several other product ions (detected especially in MS/MS spectra related to peaks #1, since they were the most abundant ones for both compounds) through neutral losses described in the scheme. Not surprisingly, fragmentation pathways leading to those product ions were generally similar to those previously observed for the aglycones of oleuropein and ligstroside [17,18].…”
Section: Demethyl-oleuropein and Demethyl-ligstrosidesupporting
confidence: 77%
See 2 more Smart Citations
“…The latter were able to explain the generation of several other product ions (detected especially in MS/MS spectra related to peaks #1, since they were the most abundant ones for both compounds) through neutral losses described in the scheme. Not surprisingly, fragmentation pathways leading to those product ions were generally similar to those previously observed for the aglycones of oleuropein and ligstroside [17,18].…”
Section: Demethyl-oleuropein and Demethyl-ligstrosidesupporting
confidence: 77%
“…The key step for the generation of secoiridoid isoforms with a C 8 =C 10 bond is the subsequent re-opening of cyclic structures generated by 1,4-intramolecular Michael addition. Indeed, this process can either return open structures with the original C 9 =C 10 bond or new open structures in which the C=C bond is located between C 8 and C 10 [17,18]. These reactions likely occur in the first stages of the olive oil production (especially during drupes crushing and malaxation) and might be modulated by the specific conditions adopted during those stages, thus explaining why the incidence of secoiridoid isoforms with a C 8 =C 10 bond can change remarkably between different olive oils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a detailed characterization of the complex set of isomeric forms found for major secoiridoids present in olive oil has been reported by Abbattista et al using an hybrid quadrupole-Orbitrap mass spectrometer, capable of high collisional energy MS/MS analyses under high resolution/accuracy conditions, and implementing H/D exchange experiments to recognize stable enolic tautomers related to aglyconic secoiridoids [110,111]. The described approach appears very promising for the search for isomeric secoiridoids also in olive leaves extracts.…”
Section: Olive Leavesmentioning
confidence: 96%
“…Although quantitative analysis showcased higher concentration of phenols and flavonoids in the leaves and roots from organo-mineral-supplemented plants, these spectrophotometric tests promote the overlapped detection of both the glycoside as well as the aglycone of secondary metabolites (Abbattista et al, 2019;Akimoto et al, 2017). Considering that the participation of secondary metabolites in biochemical processes in plants occurs mostly as glycosylated compounds (Jamwal et al, 2018), it can be suggested that the lower relative abundances of the aglycone signals in the supplemented leaves and roots therefore hints that these compounds predominate as glycosides.…”
Section: Discussionmentioning
confidence: 99%